Theoretical and Simulation Studies on Water-Loaded Metal Diagonal Horn Antenna for Hyperthermia Application - Singh, Soni; Singh, Surya P. (Electromagnetics Academy, 2015)
This paper is a continuation of our previous published work in which a water-loaded metal diagonal horn antenna has been designed at 2450 MHz for hyperthermia application and simulated results are compared with those measured. In the present study, theoretical investigations of Specific Absorption Rate (SAR) distribution in a homogeneous biological phantom (muscle) due to direct contact water-loaded metal diagonal horn antenna at 915 and 2450 MHz for hyperthermia application is presented. It is estimated theoretically that, at both the operating frequencies, a reasonable impedance matching is achieved at the interface between the antenna aperture and the biological phantom, where a computation of aperture admittance and reflection coefficient has been performed. Furthermore, it is confirmed through theoretical and simulation studies that the proposed horn antenna gives circularly symmetric SAR distribution in transverse plane in the biological phantom at 915 and 2450 MHz. The simulated and theoretical SAR distributions at 2450 MHz are compared with those determined at 915 MHz. In addition, thermal simulation results based on Pennes’ Bio-heat equation (BHE) are applied to the realistic muscle model at 915 and 2450 MHz. The reduction of blood flow rate on temperature distribution is also studied.
Keywords: hyperthermia; Horn antennas; Water absorption; Aperture admittances